Regeneration of Used Frying Palm Oil by Inorganic Adsorbent Combinations - Sonkaew, R.; Chaisena, A. (Asian Journal of Chemistry, 2011)
Used frying palm oil was treated with ten binary-blend adsorbents composed of silica, alumina, zeolite Na4A, magnesium silicate and activated carbon. These compounds' efficacy in regenerating the oil was evaluated in terms of their effects on peroxide value, p-anisidine value, free fatty acids value, total polar compounds, colour and viscosity. Of the initial binary adsorbent combinations, two were selected as providing the most significant reductions in oil parameters: activated carbon:alumina and activated carbon:silica (2:1). These two binary adsorbents were then reused over the course of 15 frying cycles to test their efficiency in removing the products of oil decomposition for all of the parameters monitored. After the used binary adsorbents were treated by calcinations at 500 ºC for 3 h, we observed a decrease in the absorption capacity of the reactivated adsorbents with regard to peroxie value, p-anisidine value, free fatty acids value, total polar compounds, total colour difference and viscosity values.